Where Have We Been and Where Are We Going in Global Health for Women and Children?. Issue 2 (March 2016) - Callister, Lynn Clark
Abstract : There have been great improvements in the health of women and children around the world in the first 15 years of the new millennium, but much more work needs to be done to promote and support optimal health for all women, mothers, children, and babies worldwide.